2020
DOI: 10.3390/agronomy10081201
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Red Light (RL) and Effective Microorganism (EM) Application on Soil Properties, Yield, and Quality in Wheat Cultivation

Abstract: The aim of the study was to determine the impact of red light (RL) and effective microorganisms (EMs) on the wheat yield of grain and straw, as well as the quality (protein, carbohydrates, gluten, index of sedimentation (SDS index), germination capacity). Moreover, the experiments measured the granulometric composition and pH of soil, as well as its content of microelements and major nutrients, including heavy metals. The field experiment was conducted in 2017, 2018, and 2019 at the experimental station (Felin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…A lot of studies which have been conducted so far showed a positive influence of a pre-sowing treatment of seeds with physical stimulants (laser light, magnetic and electric fields, gamma radiation, etc.) on the stimulation of germination, initial development and yielding of selected cereals [11][12][13][14][15][16]. Reports available in literature also mention increased content of photosynthetic pigments [17][18][19][20][21] and increased protein concentration [17,20] in crops and vegetables grown from seeds subjected to electromagnetic stimulation prior to sowing.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies which have been conducted so far showed a positive influence of a pre-sowing treatment of seeds with physical stimulants (laser light, magnetic and electric fields, gamma radiation, etc.) on the stimulation of germination, initial development and yielding of selected cereals [11][12][13][14][15][16]. Reports available in literature also mention increased content of photosynthetic pigments [17][18][19][20][21] and increased protein concentration [17,20] in crops and vegetables grown from seeds subjected to electromagnetic stimulation prior to sowing.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon may result from the activity of microorganisms contained in the preparation, which accelerated the decomposition of organic compounds and the release of nutrients from the soil. On the other hand, Szymanek et al [82] reported a negative impact of EM on the amount of available forms of soil phosphorus, potassium, and magnesium. Likewise, long-term studies by Pranagal et al [71] did not confirm the positive effect of EM on the physical properties of the soil, and the application of the preparation led to a decrease in the content of organic carbon in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a study on He-Ne light stimulation, the processing intensified the response to drought in wheat seedlings [Qiu et al 2017]. Influence of red light (RL) and the use of effective microorganisms (EM) was observed in a study on the growth, grain and straw yield in two wheat cultivars [Szymanek et al 2020]. Michtchenko and Hernández [2010] observed an increase in the number of wheat seeds germinating correctly and decrease in those germinating incorrectly under the influence of stimulation with laser light at the wavelength of 980 nm with exposure time of 30 and 60 s.…”
Section: Discussionmentioning
confidence: 99%